2017
DOI: 10.1089/bfm.2017.0003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daily Iron Supplementation in Healthy Exclusively Breastfed Infants: A Systematic Review with Meta-Analysis

Abstract: Limited available evidence suggests that daily iron supplementation has beneficial effects on hematologic parameters and cognitive development, but may delay physical growth in healthy exclusively breastfed infants. There was no evidence to suggest that iron supplementation could cause other adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…Nonetheless, the importance of adequate iron is emphasized by this evidence relative to this vulnerable period in the infant’s and young child’s brain development and likelihood of lasting impairment without adequate iron. Further emphasizing the importance of sufficient iron during this period is a recent systematic review that reports improved psychomotor development in young infants < 6 months exclusively breastfed and supplemented with iron [ 61 ] without improvement of ID, IDA, or SF.…”
Section: U-shaped Risk For Iron Status: Concerns For Pregnant Womementioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the importance of adequate iron is emphasized by this evidence relative to this vulnerable period in the infant’s and young child’s brain development and likelihood of lasting impairment without adequate iron. Further emphasizing the importance of sufficient iron during this period is a recent systematic review that reports improved psychomotor development in young infants < 6 months exclusively breastfed and supplemented with iron [ 61 ] without improvement of ID, IDA, or SF.…”
Section: U-shaped Risk For Iron Status: Concerns For Pregnant Womementioning
confidence: 99%
“…In contrast, a recent systematic review of iron supplementation of young children (6–24 months) in developed countries found no clear benefit for growth outcomes (5/6 trials) or infant development in the first 12 months (2 trials), inconsistent findings for improvement of hematologic outcomes and no reports in any of the identified studies related to neurodevelopmental delay or improvement of hematologic indicators and clinical outcomes [ 65 ]. As noted previously, the 2017 systematic review [ 61 ] found only four randomized clinical trials (RCTs) on iron supplementation of young exclusively breastfed infants <6 months and reported both benefit in terms of psychomotor development and harm in terms of reduced growth without consistent improvement of iron status in terms of IDA, ID, or SF. In spite of the need for more evidence from well-controlled RCTs especially evaluating non-hematologic health outcomes and the relationship of improved iron status with supplementation and health outcomes, all agree that treatment of ID and IDA during pregnancy and young children is important and warranted.…”
Section: U-shaped Risk For Iron Status: Concerns For Pregnant Womementioning
confidence: 99%
“…Results from a meta-analysis, which included four randomized control trials (RCT) involving 511 infants, supported early iron supplementation [ 45 ]. Current data suggests that though iron supplementation of healthy exclusively breastfed infants may improve their iron status and cognitive development, there may be a delay in their physical growth.…”
Section: Ironmentioning
confidence: 99%
“…Current data suggests that though iron supplementation of healthy exclusively breastfed infants may improve their iron status and cognitive development, there may be a delay in their physical growth. There was no evidence to suggest iron supplementation could cause other adverse effects [ 45 ].…”
Section: Ironmentioning
confidence: 99%
“…Generally, timely Fe supplementation or complementary feeding with Fe-rich/Fe-fortified foods was necessary for the depletion of infant Fe stores after exclusive breast-feeding for 6 months (26) . However, the results of Fe supplementation trials during infancy on long-term cognitive development are inconsistent and appear to vary by different population (47)(48)(49) . There is also a concern of adverse effects of Fe supplementation, including hampering brain development, due to the excess intake of Fe (50) .…”
Section: Interpretations Of Findings and Implications For Public Healthmentioning
confidence: 99%